Implementation of the Financial Reporting System on Grand Megane Optik - Gabriella Kristalinawati; Badrul Tamam; Suhartatik; Siti Nur Farida; Nurulita Anggraeni; Siska Wulandari (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
This article discusses the analysis of the financial reporting system at the Grand Megane Optik company in Jember Regency. The purpose of this article is to explore the financial reporting system used in financial management at the Jember branch of the Grand Megane Optik company. The research method used in this article is a qualitative descriptive method with data collection through interviews, observation and document analysis. The research results show that in the financial reports of the Jember branch of the Grand Megane Optik company, this company uses the Excel application and the Point of Sales (POS) application to produce monthly financial reports which will then be sent to the head office in Surabaya. In conclusion, this article shows that the Jember branch of the Grand Megane Optik company is considering using more modern and computerized software for their business management by using POS applications to improve efficiency and business management. Thus, companies can improve their business performance and gain greater profits in the future